Students’ Re-imaginations of the Future of Higher Education in Cameroon - Etta Mercy Aki; Nguehan Simeon Boris; Echari Lisa Ebenwei (Educational Considerations, 2022)
The unprecedented changes in our society are re-shaping the future of higher education; therefore, re-imagining the future of higher education is a constructive process of development. This study is aimed at exploring the re-imaginations of students in higher education from their own analysis of their previous and current experiences at three key stages: before entry, participation, and graduation. This exploratory study collected qualitative data from 68 current students through synchronous online focused group discussions. Analysis revealed that students’ experiences position higher education in Cameroon as invisible at lower levels, providing limited opportunities and promoting dependency upon graduation. However, they hope that the future of higher education will be characterized by a strong link between higher education and lower levels that will lead to the acquisition of practical skills relevant to the context and will leave graduates self-reliant. Recommendations that go beyond developing a policy to implementation and action are equally discussed.
Keywords: Re-imaginations; future; higher education; aspirations; expectations